The Two Main Pillars in the study of Arabic Language Structure: A Library Research Study on Nahwu and Syntax as Instruments for Arabic Language Analysis Structure - Fitriyah, Safira Hasna; Rosanti, Mita; Pringadie, Lorraine Aisyah Prihatiningtyas (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Proficiency in mastering a language involves not only speaking it but also studying its linguistic rules. Ilmu nahwu and syntax are two interrelated branches of language science, though each has a different focus. Ilmu nahwu, also known as Arabic grammar, studies the changes in the endings of words (i'rab) and their effects on sentence meaning. Meanwhile, syntax, which is a part of general linguistics, examines the structure and relationships between words in forming phrases, clauses, and sentences. Simply put, ilmu nahwu focuses more on word forms and their changes, while syntax emphasizes word arrangement and how words create meaning within sentence contexts. Both are essential for understanding and analyzing language, whether Arabic or other languages.This article aims to discuss ilmu nahwu and syntax from a theoretical perspective. The method used in this research is library research, which involves reviewing relevant literature. The findings show that ilmu nahwu and syntax are foundational disciplines that must be mastered in order to properly understand the Arabic language.